Engineered packaging cell line for the enhanced production of baboon-enveloped retroviral vectors - Denise Klatt; Lucia Sereni; Boya Liu; Pietro Genovese; Axel Schambach; Els Verhoeyen; David A. Williams; Christian Brendel (Elsevier, 2024)
The baboon endogenous retrovirus (BaEV) glycoprotein is superior to the commonly used vesicular stomatitis virus glycoprotein (VSVg) for retroviral gene transfer into resting hematopoietic stem cells and lymphocyte populations. The derivative BaEVRLess (lacking the R domain) produces higher viral titers compared with wild-type BaEV, but vector production is impaired by syncytia formation and cell death of the HEK293T cells due to the high fusogenic activity of the glycoprotein. This lowers viral titers, leads to increased batch-to-batch variability, and impedes the establishment of stable packaging cell lines essential for the economical production of viral supernatants. Here, we show that knockout of the entry receptor ASCT2 in HEK293T producer cells eliminates syncytia formation, resulting in a 2-fold increase in viral titers, reduced toxicity of viral supernatants, and enables the generation of stable packaging cell lines. In successive steps, we stably integrated BaEVRLess and α-retroviral a.Gag/Pol expression cassettes and isolated clones supporting titers up to 108 to 109 infectious particles/mL, a 10-fold increase in concentrated viral titers. The additional overexpression of CD47 and knockout of β2-microglobulin in the packaging cell line are tailored for future use in in vivo gene therapy applications by reducing non-specific uptake by macrophages and the immunogenicity of viral particles.